Health Destination Branding Strategy: An Exploration of Digital Narratives in Promoting Medical Tourism in Indonesia - Riu, Isma Azis (PT Maju Malaqbi Makkarana, 2025)
Medical tourism has emerged as a significant sector in Indonesia's healthcare and tourism industries, driven by increasing global demand for affordable and high-quality medical services. However, effective health destination branding remains a challenge, particularly in leveraging digital narratives to enhance Indonesia's competitiveness in the global medical tourism market. This study explores the role of digital storytelling as a strategic tool in health destination branding, analyzing how online platforms, social media, and digital marketing shape international perceptions of Indonesia’s medical tourism offerings. Using a qualitative approach, this research examines case studies of leading Indonesian medical tourism destinations, evaluates existing digital branding strategies, and identifies gaps in current promotional efforts. Findings suggest that cohesive digital narratives—combining testimonials, expert endorsements, and cultural appeal—can strengthen Indonesia's medical tourism brand equity. The study offers practical recommendations for policymakers, healthcare providers, and marketers to optimize digital strategies, fostering trust and attracting international patients. By integrating empirical insights with branding theory, this research contributes to the growing discourse on destination marketing in the digital age, with implications for Indonesia's positioning as a competitive health tourism hub in Southeast Asia.